Teaming up main group metals with metallic iron to boost hydrogenation catalysis - Christian Färber; Philipp Stegner; Ulrich Zenneck; Christian Knüpfer; Georg Bendt; Stephan Schulz; Sjoerd Harder (Nature Communications, 2022)
Elemental iron turns alkaline-earth metal complexes into highly active catalysts for the hydrogenation of alkenes, alkynes, imines and arenes. The proposed mechanism combines homogeneous catalysis by a soluble main group metal hydride complex with heterogeneous catalysis at the iron surface.